Complex polymeric nanomicelles co-delivering doxorubicin and dimethoxycurcumin for cancer chemotherapy. (31st December 2022) - Sohail, Muhammad; Yu, Bin; Sun, Zheng; Liu, Jiali; Li, Yanli; Zhao, Feng; Chen, Daquan; Yang, Xin; Xu, Hui
Abstract: Combinational therapy is a new trend in medical sciences to achieve a maximum therapeutic response of the drugs with a comparatively low incidence of severe adverse effects. To overcome the challenges of conventional formulations for cancer chemotherapy, a polymer-based complex nanomicellar system, namely CPM-DD, was developed co-delivering the anti-cancer agent doxorubicin (DOX) and potent antioxidant dimethoxycurcumin (DiMC). The optimal mass ratio of DOX/DiMC in CPM-DD was determined as 1:6 due to the synergistic antiproliferative effect from in vitro cytotoxicity assay, while the biocompatible diblock copolymer of mPEG2000-PLA5000 was selected for drug entrapment at an optimal feeding ratio of 9:1 to both drugs together. The uniform particles of CPM-DD with suitable particle size (∼30 nm) and stable drug loading content (>9%) could be reliably obtained by self-assembly with the encapsulation yield up to 95%. Molecular dynamics simulation revealed the interaction mechanism responsible for forming these complex nanomicelles. The acid-base interaction between two drugs would significantly improve their binding with the copolymer, thus leading to good colloidal stability and controlled drug release characteristics of CPM-DD. Systematic evaluation based on the MCF-7 breast tumor-bearing nude mice model further demonstrated the characteristics of tissue biodistribution of both drugs delivered by CPM-DD, which were closely related to the drug loading pattern and greatly responsible for the improved anti-cancer potency and attenuated toxicity of this complex formulation. Therefore, all the findings indicated that CPM-DD would be a good alternative to the conventional formulations of DOX and worthy of clinical application for cancer chemotherapy.